Obesity in a cohort of black Jamaican children as estimated by BMI and other indices of adiposity - Gaskin, P S; Walker, S P (European journal of clinical nutrition, 2003)
Objective : To examine the relationships of body mass index (BMI) to obesity indices derived from anthropometry and to determine tracking of overweight between late childhood and early adolescence, in a cohort of children with mixed nutritional history. We also compared identification of overweight children using The International Obesity Task Force (IOTF) BMI cut-off points with skinfolds. Design : Prospective study. Setting : Kingston, Jamaica. Subjects : A total of 306 children examined at 7–8 y and at 11–12 y. Measurements : Triceps (TSF) and subscapular skinfolds (SSF), height and weight were measured. The sum of the skinfolds (sum SF), BMI, percentage body fat (%fat) and fat mass (FM) were calculated. Pubertal stage was assessed at 11–12 y. Results : Overweight increased from 3.5 to 9.5% over the follow-up period. BMI was better correlated with the other indices of adiposity in girls and in the older age group. BMI tracking over follow up was high. In regression analysis BMI explained 52 and 61% of the variance in FM in boys and girls at 7–8 y. This increased to 69% in both sexes at 11–12 y. Using the IOTF cut-off points BMI had low sensitivity to identify children >85th percentile of the NHANES references for SSF. The sensitivity for those assessed by TSF and sum SF was higher, but between 14 and 30% of the children were misclassified. The specificity of BMI was high. Conclusions : Adiposity increased over follow-up. Although the cohort remained relatively lean BMI rank among the fattest children was maintained. Girls were fatter than boys, reflecting adult obesity patterns. Children identified as overweight by the IOTF BMI cut-off points are likely to have high body fatness. However the BMI cut-off points may not identify many children with high body fatness. Sponsorship : Nutricia Research Foundation and the Wellcome Trust (grant no. 049235/Z/96/Z).